Table of contents, editorial board, and other front matter - Curtis E. Paulson (Journal of Applied Communications, 1989)
Editorial front matter and table of contents for vol.73, no. 2 (1989) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education